1995
DOI: 10.1007/bf00223863
|View full text |Cite
|
Sign up to set email alerts
|

Double autosomal/gonosomal mosaic aneuploidy: study of nondisjunction in two cases with trisomy of chromosome 8

Abstract: We report cytogenetic and molecular investigations performed in two cases of mosaic trisomy 8 combined with mosaic sex chromosome aneuploidy. In a 35-year-old female, presenting with short stature, gonadal dysgenesis, and a multiple congenital anomalies/mental retardation syndrome typical of trisomy 8, chromosome analysis from peripheral lymphocytes showed the presence of three cell lines, whose karyotypes were 45,X (59.2%), 46,X,+8 (1.2%), and 47,XX,+8 (39.6%), respectively. The same cell lines were found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…29 Studies of trisomy 8 mosaicism in live births have demonstrated 12 cases of mitotic duplication and only one case of probable meiotic origin. 14,25,28,29 Three cases of confined placental mosaicism involving trisomy 8 ascertained through mothers undergoing CVS for advanced maternal age also showed somatic (postmeiotic) origin of the trisomic cell line, 30 as expected in theory. 15 Our results add 20 mitotic cases (including five seemingly nonmosaic cases: two live births, two spontaneous abortions, one CVS) and two maternal meiotic cases (two non-mosaic spontaneous abortions) ( Table 2).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…29 Studies of trisomy 8 mosaicism in live births have demonstrated 12 cases of mitotic duplication and only one case of probable meiotic origin. 14,25,28,29 Three cases of confined placental mosaicism involving trisomy 8 ascertained through mothers undergoing CVS for advanced maternal age also showed somatic (postmeiotic) origin of the trisomic cell line, 30 as expected in theory. 15 Our results add 20 mitotic cases (including five seemingly nonmosaic cases: two live births, two spontaneous abortions, one CVS) and two maternal meiotic cases (two non-mosaic spontaneous abortions) ( Table 2).…”
Section: Discussionsupporting
confidence: 51%
“…16,20 Looking only at the mitotic cases in our study, the skewed sex ratio persists (15M:5F). A postzygotic (mitotic) duplication of a chromosome 8 in the early embryo would be expected to occur equally frequently Data from the literature 14,25,[28][29][30] and present study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Tissue-specific mosaicism, as well as the potential for uniparental disomy as a result of trisomy rescue, were invoked as possible explanations (Nucaro et al, 2003). CT8M was found to be mostly due to mitotic nondisjunction error in live-born infants (Robinson et al, 1993;DeBrasi et al, 1995;James and Jacobs, 1996;Seghezzi et al, 1996;Karadima et al, 1998). Meiotic errors were thought to only result in miscarriages (James and Jacobs, 1996;Karadima et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…In one molecular study [9], 4 spontaneous abortions showing 100% trisomic cells were all of maternal meiotic origin, while 1 liveborn with apparent nonmosaic trisomy 8 was consistent with a mitotic gain of the extra chromosome. Studies of trisomy 8 mosaicism in liveborns have demonstrated 9 cases of mitotic duplication and only 1 case of meiotic origin [9,28,29]. Three cases of confined placental mosaicism involving trisomy 8 ascertained through mothers undergoing chorionic villus sampling for advanced maternal age also showed somatic (postmeiotic) origin of the trisomic cell line [30], as expected form theoretical considerations [31].…”
mentioning
confidence: 86%